THE ROLE OF INFORMATION TECHNOLOGY IN EDUCATION - Obidova Gullola Orifjan's daughter; Aldashev Ilhomjon Tokhtaboyevich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: Today, it is in the field of education as well as other fields Information technologies are widely entering the educational process It plays an important role in increasing the efficiency and increasing the intellectual potential. Today, life cannot be imagined without information media and the Internet. The role of the education system in the conditions of Uzbekistan's independence is primarily related to the implementation of information technologies in the education and training system.